A Novel Framework for Routine Versus Critical Communication in Surgical Education—Don't Take It Personally. Issue 3 (1st February 2023) - Falk, David; Cline, Preston; Donegan, Derek; Mehta, Samir
Abstract : Despite their impressive academic track records and mastery of controlled classroom-based didactic learning, many orthopaedic surgery residents struggle to adjust from learning in the classroom environment in medical school to learning in the operating room as surgical residents. Instead of learning in lectures, surgical residents take on a more apprenticeship-based role with the goal of mastering technical skills in an experiential learning environment. Yet, no framework has been explicitly described in the literature to help learners make this transition. Consequently, we feel there is a need to clearly define the different learning environments and modes of communication, such that the residents can better understand how information is acquired and retained as well as how feedback is delivered in the operating room compared with more traditional spaces (eg, medical school classroom). The objectives of this summary are to (1) identify the major differences between learning in the classroom environment and the operating room and (2) introduce the concept of routine versus critical communication. We hope that by better defining the new learning environment with an emphasis on communication styles that may be encountered in this setting, learners can more easily make the transition from high-performing academicians to high-performing surgeons.